Willingness to Use Self-Service Technologies Innovation on Omnichannel - Sunisa Junsawang; Singha Chaveesuk; Wornchanok Chaiyasoonthorn (My University, 2021)
Omnichannel includes innovations in Self Services technologies such as Augmented Reality, Virtual Reality, Amazon-Whole Foods, Amazon Go, Amazon Go Grocery, etc. This paper aims to develop a conceptual framework using ECM and UTAUT2 of customer willingness to use Self Services Technologies. In the end, this will provide insight into the factors that initially influence the willingness to use Self Services Technologies Innovation on Omnichannel. This conceptual framework contains eight potential constructs and expected two moderating variables to help develop and analyze a model of willingness to use Self-Service Technology Innovation using structural equation modeling.
Keywords: Consumer Retail Behavior Studies; AI in Service Interactions; Technology Adoption and User Behaviour